Understanding autism and other neurodevelopmental disorders through experimental translational neurobehavioral models. (June 2016) - Homberg, Judith R.; Kyzar, Evan J.; Nguyen, Michael; Norton, William H.; Pittman, Julian; Poudel, Manoj K.; Gaikwad, Siddharth; Nakamura, Shun; Koshiba, Mamiko; Yamanouchi, Hideo; Scattoni, Maria Luisa; Ullman, Jeremy F.P.; et al.
Highlights: Neurodevelopmental disorders are common and widespread psychiatric illnesses. Autism and other neurodevelopmental deficits often occur in early development. Animal models are a valuable tool to study autism and other neurodevelopmental disorders. We parallel clinical and preclinical data to gain a translational perspective of these illnesses. Abstract: Neurodevelopmental disorders (NDDs) are highly prevalent and severely debilitating brain illnesses caused by aberrant brain growth and development. Resulting in cognitive, social, motor, language and affective disabilities, common NDDs include autism spectrum disorder (ASD), intellectual disability, communication/speech disorders, motor/tic disorders and attention deficit hyperactivity disorder. Affecting neurogenesis, glia/neuronal proliferation and migration, synapse formation and myelination, aberrant neural development occurs over a substantial period of time. Genetic, epigenetic, and environmental factors play a key role in NDD pathogenesis. Animal models are an indispensable tool to study NDDs. Paralleling clinical findings, we comprehensively evaluate various preclinical tests and models which target key (social, cognitive, motor) neurobehavioral domains of ASD and other common NDDs. Covering both traditional (rodent) and alternative NDD models, we outline the emerging areas of research and emphasize how preclinical models play a key role in gaining translational and mechanistic insights into NDDs and their therapy.